1991
DOI: 10.1210/endo-128-4-2091
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Ductal System in Rats: Regional Variation in Localization of an Androgen-Repressed Gene Product, Sulfated Glycoprotein-2*

Abstract: The rat prostate is a complex ductal system with branches and subbranches extending from one end to another. Owing to the relative distance of various regions from the urethra, the entire length of the ductal system can be divided into three segments, i.e. the proximal, intermediate, and distal segments. The present study was carried out to examine the pattern of localization of sulfated glycoprotein-2 (SGP-2), a marker protein associated with programmed cell death, in various regions of the prostatic ductal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 0 publications
8
69
0
2
Order By: Relevance
“…Rather, in agreement with other results [24,25], the high constitutive level of expression in REtsAF-Revl suggests a protective role for clusterin. Apoptosis of REtsAF cells in restrictive conditions appears to involve the release of p53 activity [5].…”
Section: Discussionsupporting
confidence: 91%
“…Rather, in agreement with other results [24,25], the high constitutive level of expression in REtsAF-Revl suggests a protective role for clusterin. Apoptosis of REtsAF cells in restrictive conditions appears to involve the release of p53 activity [5].…”
Section: Discussionsupporting
confidence: 91%
“…It is known that clusterin is expressed in both benign and malignant prostatic epithelial cells. 14,21 Clusterin can also be expressed in prostatic stromal cells. 22 Therefore, the staining intensity was evaluated separately in following four distinct types of cells: (a) benign epithelium, (b) cancerous epithelium, (c) stroma associated with benign epithelium, and (d) stroma associated with cancerous epithelium.…”
Section: Resultsmentioning
confidence: 99%
“…It therefore could serve as a valuable model of human prostate cancer, allowing one to address the role of p53 in prostate cancer biology, including its sensitivity to anti-cancer therapy both by chemotherapeutic drugs and physiological regulators of cell proliferation and survival. It has been reported that LNCaP is highly sensitive to the cytotoxic eect of TNF-a (Nakajima et al, 1996;Sensibar et al, 1995;Zhao et al, 1992). TNF-a is a cytokine capable of initiating a broad range of biological eects including apoptosis of some tumor cells (reviewed in Wong et al, 1997).…”
Section: Introductionmentioning
confidence: 99%